Navigating the introduction of anti-amyloid therapy in Europe: a position statement by individual members of the EADC - Frederiksen, Kristian Steen; Boada, Mercé; Dubois, Bruno; Engelborghs, Sebastiaan; Frisoni, Giovanni B.; Georges, Jean; Hort, Jakub; Jönsson, Linus; Kramberger, Milica G.; Ousset, Pierre-Jean; Scarmeas, Nikolaos; Schmidt, Reinhold; et al. (Alzheimer's research & therapy, 2025)
Anti-amyloid antibodies for the treatment of Alzheimer´s disease (AD) are currently being evaluated for approval and reimbursement in Europe. An approval brings opportunities, but also challenges to health care systems across Europe. The objective of this position paper is to provide guidance from experts in the field in terms of navigating implementation.